MEGENGAN DAN MALAMANG: Studi Perbandingan Tradisi Penyambutan Ramadan dalam Perspektif Fungsionalisme - Sari, Indah Puspita (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
Indonesia is inhabited by people who are predominantly Muslim. The month of Ramadan is a month that Muslims look forward to. Indonesian people, especially in East Java and West Sumatra, have a tradition of welcoming the month of Ramadan, namely the megengan tradition and the malamang tradition. Megengan in East Java is done by praying together and distributing food, especially apem cakes, while malamang is done by making lemang together. The megengan and malamang traditions are a form of Indonesian people's joy in welcoming Ramadan, and these traditions reflect cultural and Islamic values. The purpose of this paper is to compare megengan and malamang as a form of tradition to welcome the holy month of Ramadan. The method used is a qualitative method with data collection techniques in the form of literature study. The theory used is functionalism, developed by Bronislaw Malinowski and A.R. Radcliffe-Brown. As a result, these two traditions are traditions carried out by the community as a form of welcoming the arrival of the month of Ramadan, which is carried out collectively by the community and contains Islamic values such as friendship, cooperation, and togetherness. Both traditions are carried out by every element of society, from children to the elderly.